2009
DOI: 10.2355/isijinternational.49.709
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Texture Features and Mineralogy Phases in Iron Ore Sinter Based on Gray-level Co-occurrence Matrix

Abstract: An intelligent recognition and quantification system for photomicrographs of iron ore sinter is useful and convenient; however, it is impossible to develop a successful intelligent system without adequate and accurate texture features of mineralogical phases. The gray-level co-occurrence matrix (GLCM) has been proved as an effective method for extracting the texture features in other fields, therefore, this work examines texture features for the main mineralogical phases, such as magnetite and calcium ferrite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Whereas, if it is too small, it may not sufficiently extract the texture feature. Lv et al 2009 suggested that contrast, energy and homogeneity change less when an image window was over 75 pixels. Therefore, a window size of 100 × 100 was used.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, if it is too small, it may not sufficiently extract the texture feature. Lv et al 2009 suggested that contrast, energy and homogeneity change less when an image window was over 75 pixels. Therefore, a window size of 100 × 100 was used.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the image processing techniques based on the evaluation of the shades of grey are also limited to dividing the minerals in examined sinter samples just into main groups, i.e. hematite, magnetite, Ca-ferrites, silicates and pores [15,[18][19][20]. This means that the distinction between calcium ferrite types is also not involved.…”
Section: Discussionmentioning
confidence: 99%
“…Most of researches of phase composition realized today is still based on image analysis, where only shades of grey and shape of crystal can observed. 10,11) Many classify calcium ferrites according to that.…”
Section: )mentioning
confidence: 99%